2020
DOI: 10.1101/2020.02.10.942540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remote-controlled insect navigation using plasmonic nanotattoos

Abstract: and singamaneni@wustl.edu Developing insect cyborgs by integrating external components (optical, electrical or mechanical) with biological counterparts has a potential to offer elegant solutions for complex engineering problems. 1 A key limiting step in the development of such biorobots arises at the nano-bio interface, i.e. between the organism and the nano implant that offers remote controllability. 1,2 Often, invasive procedures are necessary that tend to severely compromise the navigation capabilities as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Those solutions were mainly based on direct or indirect electrical stimuli. Other different types of actuators have been proposed based on: (i) thermal stimulus considering different species of beetles [39], (ii) optrodes to control the flight of dragonfly based on flexible waveguide arrays [40], (iii) biochemical molecules for muscle relaxation by a specific type of liposome [41] , (iv) plasmonic nanotattoos [42], (v) artificial claw open-close cycle mechanism [43], and (vi) explosive chemical vapors [44].. Actuation in cyborg insects poses ethical questions that have been systematically indicating in [45]. Different domains are identified and the effects of the media coverage is mapped, trying to indicate different types of application with their moral judgment.…”
Section: B Domestication Of Movementsmentioning
confidence: 99%
“…Those solutions were mainly based on direct or indirect electrical stimuli. Other different types of actuators have been proposed based on: (i) thermal stimulus considering different species of beetles [39], (ii) optrodes to control the flight of dragonfly based on flexible waveguide arrays [40], (iii) biochemical molecules for muscle relaxation by a specific type of liposome [41] , (iv) plasmonic nanotattoos [42], (v) artificial claw open-close cycle mechanism [43], and (vi) explosive chemical vapors [44].. Actuation in cyborg insects poses ethical questions that have been systematically indicating in [45]. Different domains are identified and the effects of the media coverage is mapped, trying to indicate different types of application with their moral judgment.…”
Section: B Domestication Of Movementsmentioning
confidence: 99%
“…One of the most critical tasks of the hybrid robot's development process is insect motion control. In recent years, there has been an influx of work investigating the development of protocols for insect movement control [13][14][15][16][17][18][19] . Ma et al demonstrated that locust jumping movements can be induced by stimulating their leg muscles 19 .…”
mentioning
confidence: 99%